2019
DOI: 10.1038/s41467-019-11427-y
|View full text |Cite
|
Sign up to set email alerts
|

Engineered ribosomes with tethered subunits for expanding biological function

Abstract: Ribo-T is a ribosome with covalently tethered subunits where core 16S and 23S ribosomal RNAs form a single chimeric molecule. Ribo-T makes possible a functionally orthogonal ribosome–mRNA system in cells. Unfortunately, use of Ribo-T has been limited because of low activity of its original version. Here, to overcome this limitation, we use an evolutionary approach to select new tether designs that are capable of supporting faster cell growth and increased protein expression. Further, we evolve new orthogonal R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 55 publications
3
66
0
Order By: Relevance
“…2a, b). In the resulting OSYRIS cells, the Ribo-T rRNA with improved 16S-23S tethers 17 is expressed from the optimized pRibo-Tt plasmid. Another plasmid, poRbs, carries the rRNA genes of the dissociable o-ribosomes, whose 16S rRNA gene has an altered ASD ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2a, b). In the resulting OSYRIS cells, the Ribo-T rRNA with improved 16S-23S tethers 17 is expressed from the optimized pRibo-Tt plasmid. Another plasmid, poRbs, carries the rRNA genes of the dissociable o-ribosomes, whose 16S rRNA gene has an altered ASD ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…a Organization of rRNA genes and structure of the dissociable 70S ribosome (left) and Ribo-T (right). The small and large subunits of Ribo-T are covalently linked by two RNA tethers connecting circularly-permutated 23S rRNA to the loop of helix 44 in 16S rRNA 14,17 . The sequences of 16S rRNA sequences are shown in olive and those of 23S rRNA in gray.…”
Section: Ribo-tmentioning
confidence: 99%
See 1 more Smart Citation
“…Ribo-T ribosomes are present, but only the Ribo-T ribosomes can initiate lacZ translation, because of the mutated SD sequence. Crosstalk between wild-type ribosomes and the orthogonal mRNA has recently been described 8 . We checked the level of crosstalk in our system, and found that it was too low to affect the results.…”
Section: Gaccgtaatcatggtatattgtggtgttaaagttaaacaaaattatttc-3'mentioning
confidence: 99%
“…Recently, engineering mutant ribosomes to elucidate key principles underpinning the process of translation, program cellular function, and generate novel sequence-defined polymers has emerged as a major opportunity in chemical and synthetic biology [1][2][3][4][5][6][7] . Although efforts to engineer ribosomal function have achieved some success 8,9 , especially with the recent advance of tethered ribosome systems [10][11][12] , a significant repurposing of the translation apparatus is constrained by challenges inherent to altering translation in living cells. A completely in vitro approach could overcome cell viability constraints to repurpose the ribosome into a re-engineered machine for understanding, harnessing, and expanding the capabilities of the translation apparatus.…”
mentioning
confidence: 99%